2014
DOI: 10.1177/1045389x14535012
|View full text |Cite
|
Sign up to set email alerts
|

Application of single unit impact dampers to harvest energy and suppress vibrations

Abstract: In this study, ongoing investigations to apply piezoelectric materials as an energy harvester are extended. In doing so, effectiveness of single unit impact dampers is increased using piezoelectric materials. For this reason, barriers of the impact damper are replaced with cantilever beams, which are equipped with the piezoelectric patches. For convenience, this kind of impact dampers is named as “piezo-impact dampers.” The piezo-impact damper is not only a vibration suppressor but also it is an energy harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Finally, the concept of impact dampers using a moving mass and piezoelectric beams was discussed by Afsharfard and Farshidianfar. 16 In our case, the moving mass made of steel coupled to a vertical cantilever laminate beam ( Figure 1) would create impact and friction phenomena. In general, the non-linear effects improve the effectiveness of energy harvesting systems by broadening frequency intervals in the resonance region.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, the concept of impact dampers using a moving mass and piezoelectric beams was discussed by Afsharfard and Farshidianfar. 16 In our case, the moving mass made of steel coupled to a vertical cantilever laminate beam ( Figure 1) would create impact and friction phenomena. In general, the non-linear effects improve the effectiveness of energy harvesting systems by broadening frequency intervals in the resonance region.…”
Section: Introductionmentioning
confidence: 91%
“…Finally, the concept of impact dampers using a moving mass and piezoelectric beams was discussed by Afsharfard and Farshidianfar. 16…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the optimized periodic time-varying damper could harvest more power at off-resonance compared to an arbitrary periodic time-varying damper, which was chosen to have the same transmissibility at resonance. Afsharfard et al [181] used piezoelectric elements as single unit impact dampers, which was capable of vibration control while EH. An analytical approach was presented to formulate the voltage generation and the vibrations suppression.…”
Section: Simultaneous Energy Harvest and Controlmentioning
confidence: 99%
“…For example, Abdelkefi et al (2012a) presented a theoretical analysis using a wake-oscillator model to describe fluid forces on the oscillating circular cylinder which is appropriately coupled with the cylinder and piezoelectric dynamics. Additionally, Akaydin et al (2012) also presented an experimental approach. Energy harvesting from oscillations of a circular cylinder in the wake of a fixed upstream cylinder has been experimentally studied by Nishi et al (2014) and by Jung and Lee (2011), where electromagnetic conversion was used.…”
Section: A New Paradigm Flow Induced Vibrations As An Energy Harvestmentioning
confidence: 99%
“…Note that motion occurs also along the in-line flow direction. To describe the backlash electromechanical force caused by the effect of the piezoelectric sheets, let us consider a lumped model such as the one developed and tested in references Erkturk (2009), Shu and Lien (2006), Akaydin et al (2012), Afsharfard et al (2014) or Wang and Lu (2014). This model considers that a triple-layer bender is mounted on a cantilever beam with polarization poled along the thickness direction, (Fig.…”
Section: Mathematical Modelmentioning
confidence: 99%